ANALISIS HUBUNGAN ANTARA KEGIATAN MELUKIS DENGAN KEBUTUHAN PSIKOLOGIS PADA REMAJA - Shokiyah, Nunuk Nur (Institut Seni Indoensia Surakarta, 2014)
This research aims to learn the correlation between painting activities and psychological needs of theteens. There are two variables in this research covering painting activities as the independent variableand psychological needs as the dependent variable. The correlation technique of Product MomentPearson is used to know the correlation between painting activities and the psychological needsof the teens, while the calculation uses the computer program SPSS 15 for windows release. Subjectof this research is all active students of the Pure Fine Arts Department in Institut Seni IndonesiaSurakarta. All data that is collected covers 61 subjects. The measuring instrument used is the intensityscale of painting activities and the scale of psychological needs. The result of this research showsthe coefficient correlation (rxy = 0,746; p = 0.000), it means that there is a significant correlationbetween the painting activities and the psychological needs to the teens. Meanwhile, the determinationcoefficient of the correlation is R2 is 0,556. It means that the painting activities give the effectivecontribution to the psychological needs to the teens as much as 55,6 % while the rest of 44,6 % isdetermined by other variables.Keywords: painting activities, psychological needs.